Travelling Expenses: The Energy Cost of Diel Vertical Migrations of Epipelic Microphytobenthos - Marques da Silva, Jorge; Duarte, Bernardo; Utkin, Andrei Borissovitch (Frontiers in Marine Science, 2020)
The physiology of the diel movements of epipelic microphytobenthic diatoms is not fully understood. As well, the evolutionary pressures that led to migratory behavior and the ecological role of vertical migrations remain unknown. The behavioral photoprotection hypothesis, according to which the diatoms move along the vertical light gradient to find their optimal light environment, is the most generally accepted. However, the motion is associated with an energy cost that has not been fully acknowledged before. To throw light on this issue, we looked at the mechanisms of diatom locomotion and reviewed their patterns of movement. Making use of published data, we estimated an energy cost of 0.12 pJ for a typical diatom cell to move upward (or downward) in a 400 µm photic zone. This amounts to 3.93x10-18 mol of ATP, which are released by the oxidation of 1.31 x10-19 mol of glucose. This represents only 0.0001% of the daily net photosynthetic production of a typical microphytobenthic diatom cell, showing that diel vertical migrations have a negligible impact on cell and ecosystem energy budget. Even though the migration energy cost of individual cells may depart almost two orders of magnitude from the central value presented for a typical diatom (depending on cell size, velocity of displacement and viscosity of the medium), the maximum value calculated is still negligible from the metabolic and ecologic point of view. Results show that behavioural photoprotection might be an energetically cheap mechanism, offering competitive advantages when compared with structural/physiological photoprotection.